مشروع الحكومة الإلكترونية في دولة الكويت : بيت الزكاة - حالة عملية - الدويان، فاطمة صالح (جامعة حسيبة بن بو علي بالشلف - مخبر العولمة واقتصاديات شمال إفريقيا, 2008)
It is the era of information, communication and technology. The whole world is full aware of desperate need to move toward sophistication. It becomes a must. A very flourishing example is E – Government. Based on that need, Kuwait Council of Ministers issued Act/nr. 759 establishing the National Committee for applying sophisticated technology into public sector (chaired by the Prime Minister). As long as the matter is very important, the study tried to present the Kuwaiti experience in dealing with this project. With an emphasis on a real case from the public sector that proceed few steps toward entering the portal of Kuwait e-government. It is an effort to identify and evaluate an experience, through discussing the following elements: • Bases to move from manual to technological work. • Factors for successful e-government. To enhance positives and eliminate negatives. • Role of state, private, civil, and co-operative sectors. Or it is a state responsibility. • Phases should be followed to get the job done (e-government project design) Applying previous elements on a public organization (Zakat House). With reviewing supporting factors and obstacles facing the project.
705864
Keywords: الإدارة الإلكترونية -- الحكومة الإلكترونية -- الكويت -- بيت الزكاة -- الإدارة العامة -- نظم المعلومات الإدارية -- شبكات المعلومات